FRAUD DAN AKUNTANSI FORENSIK (UPAYA MINIMALISASI KECURANGAN DAN REKAYASA KEUANGAN) - SAYYID, ANNISA (Islamic Economics and Business Faculty of UIN Antasari, 2013)
he accounting scandal is the real picture of the accounting frauds in the global world.These frauds are mostly difficult to detect through only regular accounting check or audit. Thisproblem has not been solved until now. Enron Corporation, Lehman Brothers bankruptcy, and thewildered situation of Citigroup feel like djvu of the Black Tuesday in 1929. Indonesia also feels thesame situation. Begins with the Century Bank unsolved case to PT Ades Alfindo and PT. Indofarmaproblematic situation. The accounting forensic is the answer of those challenges. The problembased nature of the accounting forensic is hoped to be the solution for those fraud problems and toprevent those frauds to make bigger damage for the related sides. The accounting forensic is the useof accounting skill with the investigative capability to solve a problem or a fraud suspect. In this case,fraud is the deliberate mistake to gain fortune from the other party.